Spots on the Sun and Life on the Earth - Valentina V. Ukraintseva (Journal of Basic & Applied Sciences, 2019)
The paper deals with a new integrated method of reconstruction and forecasting of climatic changes on the Earth. The method is based on proxy data pollen analysis method, fossil and recent spore-pollen spectra, 14C analysis method, basic elements of climate, Similarity Indices (SI) of solar Activity, expressed in number of Wolf’s (Wm2), and forecasting of climate changes. The techniques of reconstruction and forecasting are presented and discussed.